Pembuatan Alat Penjernihan Air Dengan Filter Bertekanan Rendah Untuk Masyarakat Desa Laut Dendang Kecamatan Percut Sei Tuan Kabupaten Deliserdang - Diana Suita; Marina Elsera; Liza Fitriana; Uun Novalia Harahap (Jurnal TUNAS, 2021)
Clean water is water that is fit for consumption. Clean water is not only clear, odorless, and tasteless, but also must meet health requirements. These health requirements, among others, do not contain toxic chemicals or bacterial germs that can interfere with health. Dirty water contains solid or liquid substances resulting from waste disposal such as garbage, carcasses, used washing water, household waste and others. Polluted water will have an impact on human health. One of the waters that has been polluted with heavy metals is in the sea village of Percut Sei Tuan District, Deli Serdang Regency. For this reason, it is necessary to treat well water in the village of Laut Dendang. There are various simple ways that can be used to get clean water, and the most common way is to make a water filter and perhaps the most appropriate is to make a water purifier or a simple water filter. It is undeniable, that simple water filtration cannot eliminate completely as water with conditions, because processing dirty water into clean water must be done carefully so that the germs in the water are completely gone. Based on the description above, socialization and manufacture of water purification equipment with low pressure filters were undertaken for the people of Laut Village, Dendang village 6 (XI), village 8 (XIII), and village 9 (IX) Percut Sei Tuan District, Deli Serdang Regency. Several other things become obstacles in making water purification equipment with low pressure filters for the field community. For this reason, an innovation is needed to manufacture water purification equipment with low pressure filters for the community and overcome obstacles or solutions for making water purification equipment with low pressure filters. The Harapan University Service Team Medanundertaken socialization activities and direct field practice on the manufacture of water purification equipment with low pressure filters for the people of Laut Village, Dendang village 6 (XI), village 8 (XIII), and village 9 (IX) Percut Sei Tuan District, Deli Regency Serdang.